Finance and Development, December 2001. (Finance and Development; Finance and Development ;, 2001)
This paper examines how Africa can reposition itself to take full advantage of globalization-while minimizing the risks in the process-to accelerate economic growth and reduce poverty. The paper highlights that Africa's share of world trade has dwindled, foreign direct investment in most countries has remained at low levels, and the income gap relative to advanced countries has widened. The paper looks at why Africa has missed out so far on the benefits of globalization, and indicates what steps Africa now needs to take to boost economic growth.